Full-depth profiles of PAHs in the Western South China Sea: Influence of Upwelling and Mesoscale Eddy. (January 2021) - Liu, Mengyang; Hu, Jiahui; Lin, Yan; Ke, Hongwei; Lian, Jiongjie; Xu, Ye; Chen, Kai; Zheng, Haowen; Chen, Mian; Cai, Minggang
Abstract: Oceanic processes such as coastal upwelling and mesoscale eddy, could influence the spatial distribution and environmental behaviors of semi-volatile organic pollutants in the marine environment. Seawater samples were collected from the full-depth water columns from the South China Sea (SCS), and PAH concentrations (∑14 PAH) in the continental shelf and the open basin areas were 16–110 and 10–93 ng/L respectively. Results of isomeric ratios and principal component analysis illustrated PAHs' mixed sources (petrogenic and pyrogenic). PAH inventory of the SCS seawater was estimated as 100 ± 58 thousand tons, and the majority of them was stored in the intermediate and deep water masses. Generally, full-depth profiles of dissolved PAHs showed an "enrichment in surface and exhaustion in the deep" pattern, and this might be influenced by the oceanic processes such as coastal upwelling or eddy diffusion. In the cross-shelf area, upwelling could enhance the scavenging efficiency of PAHs on the upper layer, and increase the pollutant concentration in the medium and deep water. While in the open-basin area, PAHs were more likely influenced by the halocline stratification and eddy diffusion, and their vertical fluxes due to eddy diffusion was estimated to be 1.2 × 10 −6  g s −1 . This study highlighted the influences of oceanic processes in transport PAHs in the marginal sea, further study is needed to investigate their seasonal variations related to the monsoon characteristics. Highlights: Depth profiles of PAHs showed an "surface-enrichment and depth-exhaustion" pattern, and mass inventories in the South China Sea were estimated as 100 thousand tons. In the cross-shelf, upwelling could enhance the scavenging efficiency, and increase the concentration in the medium and deep water. In the open-basin, halocline stratification and eddy diffusion would influence PAHs, and their vertical fluxes of eddy diffusion were about 1.2 × 10 −6  g s -1 .